2016
DOI: 10.1007/s11682-016-9552-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cognitive functions and cerebral grey matter and their associations with inflammatory markers, endocrine markers, and APOE genotypes in testicular cancer patients undergoing treatment

Abstract: Evidence suggests that testicular cancer (TC) and its treatment are associated with cognitive impairment. However, the underlying neural substrate and biological mechanisms are poorly understood. This study aimed to investigate changes in cognition and brain grey matter (GM) morphology in TC patients undergoing treatment, and to explore associations with immune markers, endocrine markers, and genotype. Sixty-five patients with stage I-III TC underwent assessment after surgery but prior to further treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 66 publications
4
71
0
Order By: Relevance
“…In addition, cognitive dysfunction, GM reduction in the left anterior cingulate cortex and the bilateral parahippocampal gyri and insula, as well as focally decrease WM integrity in bilateral inferior longitudinal fasciculi and left cingulum were found in chemotherapy-exposed subjects compared to healthy controls. A few other recent publications of structural MRI of testicular cancer [27] as well as fMRI studies of prostate [28] and various cancers [29], including breast, colorectal, Hodgkin’s lymphoma, leukemia and myeloma, similarly support the presence of structural/functional neuroimaging and cognitive abnormalities in these malignancies following treatment.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, cognitive dysfunction, GM reduction in the left anterior cingulate cortex and the bilateral parahippocampal gyri and insula, as well as focally decrease WM integrity in bilateral inferior longitudinal fasciculi and left cingulum were found in chemotherapy-exposed subjects compared to healthy controls. A few other recent publications of structural MRI of testicular cancer [27] as well as fMRI studies of prostate [28] and various cancers [29], including breast, colorectal, Hodgkin’s lymphoma, leukemia and myeloma, similarly support the presence of structural/functional neuroimaging and cognitive abnormalities in these malignancies following treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Structural [15, 19, 34] and functional MRI [23, 24, 35] studies have found that abnormalities may already exist in the absence of chemotherapy for breast cancer patients. More recent neuroimaging studies of other types of cancer including lung [26] and testicular cancer [27] also suggest that structural abnormalities exist without chemotherapy. This is further supported by neuropsychological data in breast [36, 37], testicular [27] and lung cancer [26] patients not treated with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only the number of behavioral studies remains limited for these patients, neuroimaging studies in childhood non-CNS solid tumor survivors have not been performed yet. Still, adult studies have reported alterations of the WM microstructure in solid tumor patients (including breast and testicular cancer; Ahles et al, 2014;Amidi et al, 2016;Deprez et al, 2011;Deprez, Billiet, Sunaert, & Leemans, 2013;McDonald et al, 2010). Nowadays, MR diffusion-weighted neuroimaging is used to characterize the WM microstructure, and assess possible changes after treatments.…”
mentioning
confidence: 99%
“…Indeed, in men with prostate cancer, Gonzalez et al [43■■] examined a number of these factors and found that a genetic variant on the G protein subunit beta 3 region was associated with cognitive decline in those on ADT. There has also been promising research examining genetic variants in breast and other cancer patients, showing that individuals carrying specific genetic polymorphisms of the Apoliprotein (APOE) and catechol-O-methyltransferase (COMT) genes may be at greater risk of cognitive impairment [5153]. An additional well known issue is that cognitive impairment may exist prior to the onset of systemic treatments such as hormone therapy and chemotherapy [54, 55] posing methodological challenges as hormone therapy-related effects may be confounded by other treatment and disease-related effects.…”
Section: Discussionmentioning
confidence: 99%